العلاقة بين التوجهات الهدفية وأنماط الهوية الأكاديمية لدى الطلبة المراهقين في مديرية قصبة إربد - عبابنة، محمد فلاح يوسف; صوالحة، محمد أحمد (جامعة إربد الأهلية - عمادة البحث العلمي, 2022)
هدفت الدراسة الحالية إلى الكشف عن العلاقة بين التوجهات الهدفية وأنماط الهوية الأكاديمية لدى الطلبة المراهقين في مديرية قصبة إربد. تكونت عينة الدراسة من (770) طالبا وطالبة من طلبة الصفين الثامن والأول ثانوي في مديرية التربية والتعليم في مديرية قصبة إربد خلال الفصل الدراسي الثاني من العام الدراسي 2018/2019، وقد تم اختيارهم بالطريقة العشوائية الطبقية. طبق عليهم مقياس توجهات الأهداف ومقياس الهوية الأكاديمية. أظهرت النتائج أن مستوى أهداف إتقان-إقدام جاء في المرتبة الأولى وبدرجة مرتفعة، يليه أهداف أداء-إقدام، وأهداف أداء-تجنب في المرتبة الثانية والثالثة على التوالي وبدرجة متوسطة، كما أظهرت النتائج أن مستوى نمط الهوية المنجزة (المحققة) جاء في المرتبة الأولى وبدرجة مرتفعة، يليه نمط الهوية المؤجلة ونمط الهوية المغلقة في المرتبة الثانية والثالثة على التوالي وبدرجة متوسطة، وأخيرا جاء نمط الهوية المضطربة في المرتبة الأخيرة وبدرجة منخفضة، كما أظهرت النتائج وجود علاقة ارتباطية موجبة دالة إحصائياً بين أهداف إتقان-إقدام من جهة، ونمط الهوية الأكاديمية المنجزة من جهة أخرى، وعلاقة ارتباطية سالبة دالة إحصائياً بين أهداف إتقان-إقدام ونمط الهوية المضطربة، ووجود علاقة ارتباطية موجبة دالة إحصائياً بين أهداف أداء-إقدام من جهة وبين نمط الهوية (المنجزة، والمغلقة، والمؤجلة، والمضطربة) من جهة أخرى، ووجود علاقة ارتباطية موجبة دالة إحصائياً بين أهداف أداء-تجنب من جهة ونمط الهوية الأكاديمية المغلقة والمؤجلة والمضطربة من جهة أخرى. This study aimed at exploring the relationship between the goal orientation, (GO) and the academic identity styles among adolescent students in Irbid district. The sample of the study consisted of (770) male and female students from the eighth and eleventh grades at the Directorate of Education in Irbid District for the academic year 2018/2019; the second semester. The students were chosen randomly and in a stratified manner. They were applied to the Goal Orientation Scale and the Academic Identity Scale. The results showed that the level of mastery-approach goals came first and with a high degree, followed by performance –approach goals and performance – avoidance goals in the second and third place respectively. The results also showed that the level of achievement Identity came in the first place with a high degree, then came moratorium identity and foreclosure identity in the second and third place respectively with a medium degree. Finally came the diffusion identity style with a low degree. In addition, the results showed a correlation relationship statistically positive between the mastery-approach goals and the achievement academic identity on the other hand. Besides, a negative correlation relationship significant with the style of diffused identity. They also showed a positive correlation relationship statistically significant between performance- approach goals on one hand and the style of identity (achievement, foreclosure, moratorium, diffused). Moreover, there has been a statistically significant positive relationship between performance – avoidance goals on one hand and the foreclosure moratorium and diffused academic identity styles on the other hand.
Keywords: المراهقة -- المراهقين -- الهوية الأكاديمية -- التوجهات الهدفية -- طلبة المرحلة الثانوية -- مديرية قصبة إربد -- الأردن